Delay-constrained energy-efficient routing in heterogeneous wireless sensor networks. (14th May 2010) - Yang, Yinying; Cardei, Mihaela
In this paper, we propose a routing strategy for heterogeneous wireless sensor networks, which supports both periodic and event-based reporting applications. The energy-efficient network model in this paper consists of static sensor nodes, mobile and static supernodes. We propose an energy-efficient routing protocol that can satisfy the delay requirements of different types of data messages. Each source-sensor, with data to be transmitted to the sink, chooses the best relay supernode from the candidates in its routing table such that it meets the delay requirements. The message is transmitted to the selected relay supernode using sensor-to-sensor communication, and from there to the sink using supernode-to-supernode communication. Simulation results show that our routing protocol is energy-efficient and effectively satisfies different delay requirements.